2004
DOI: 10.1002/joc.1071
|View full text |Cite
|
Sign up to set email alerts
|

Northeast monsoon rainfall variability over south peninsular India vis‐à‐vis the Indian Ocean dipole mode

Abstract: Whereas the June through to September southwest summer monsoon season over the Indian subcontinent has been the main focus of research, the October through to December northeast monsoon season over south peninsular India has received less attention. Hence, this study focuses on the northeast monsoon rainfall (NEMR) variability using historical data for a 131 year period and its relationship with the neighbouring Indian Ocean sea-surface temperature (SST).Based on the observed available rainfall data, a time s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
144
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(151 citation statements)
references
References 20 publications
6
144
1
Order By: Relevance
“…Kripalani and Kumar (2004) showed that the IOD also influences the NEMR variability. In this section, the ENSEMBLES MME results were analysed to examine whether the ENSEMBLES MME captures the observed relationship with ENSO and IOD.…”
Section: Monsoon Teleconnections In Coupled Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kripalani and Kumar (2004) showed that the IOD also influences the NEMR variability. In this section, the ENSEMBLES MME results were analysed to examine whether the ENSEMBLES MME captures the observed relationship with ENSO and IOD.…”
Section: Monsoon Teleconnections In Coupled Modelsmentioning
confidence: 99%
“…significantly above normal (63% and 55% respectively). The increasing trend in the NEMR during the recent years could be related to the increasing trend in the positive phase of the Indian Ocean Dipole Mode (Kripalani and Kumar, 2004). The inter-annual variability of the NEMR is linked to the El Niño/Southern Oscillation (ENSO), Indian Ocean Dipole and the EQUINOO (De and Mukhopadhyay, 1999;Bhanu Kumar et al, 2004;Kripalani and Kumar, 2004;Zubair and Ropelewski, 2006;Kumar et al, 2007;Sreekala et al, 2011).…”
Section: Inter-annual Variability Of the Nemr And Its Secular Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several theories have been proposed for this decadal ENSO (see Zhang et al [1997] and Luo et al [2003] for details and references). Recently, Kripalani and Kumar [2004] found decadal epochs in seasonally stratified IOD index. In this context, we here examine the possibility of the existence of a decadal IOD using observed data sets and a coupled general circulation model (CGCM).…”
Section: Introductionmentioning
confidence: 99%